PATHOPHYSIOLOGY AND FUNCTIONS OF THE KIDNEYS: AN INTEGRATIVE OVERVIEW - Turaev Umar Rahimovich (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  The  kidneys  are  essential  for  maintaining  internal  homeostasis through  their  roles  in  filtration,  reabsorption,  secretion,  and  hormone  production. Disruption in kidney function leads to a wide range of systemic complications. This review discusses the primary physiological functions of the kidneys and explores the underlying pathophysiological mechanisms in common renal diseases such as acute kidney injury (AKI), chronic kidney disease (CKD), and glomerulonephritis.